Nanoscale Plasma Coating Inhibits Formation of Staphylococcus aureus Biofilm - Xu, Yuanxi (Antimicrob Agents Chemother, 2015)
Staphylococcus aureus commonly infects medical implants or devices, with devastating consequences for the patient. The infection begins with bacterial attachment to the device, followed by bacterial multiplication over the surface of the device, generating an adherent sheet of bacteria known as a biofilm. Biofilms resist antimicrobial therapy and promote persistent infection, making management difficult to futile. Infections might be prevented by engineering the surface of the device to discourage bacterial attachment and multiplication; however, progress in this area has been limited. We have developed a novel nanoscale plasma coating technology to inhibit the formation of Staphylococcus aureus biofilms. We used monomeric trimethylsilane (TMS) and oxygen to coat the surfaces of silicone rubber, a material often used in the fabrication of implantable medical devices. By quantitative and qualitative analysis, the TMS/O(2) coating significantly decreased the in vitro formation of S. aureus biofilms; it also significantly decreased in vivo biofilm formation in a mouse model of foreign-body infection. Further analysis demonstrated TMS/O(2) coating significantly changed the protein adsorption, which could lead to reduced bacterial adhesion and biofilm formation. These results suggest that TMS/O(2) coating can be used to effectively prevent medical implant-related infections.